2014
DOI: 10.15517/pensarmov.v12i1.12651
|View full text |Cite
|
Sign up to set email alerts
|

Análisis Sobre Las Formas Corporales Y Los Patrones De Actividad Física Dominantes en Una Colección De Libros Para Colorear

Abstract: __________________________________________________________________ Resumen Martínez -Bello, V. (2014). Análisis sobre las formas corporales y los patrones de actividad física dominantes en una colección de libros para colorear. PENSAR EN MOVIMIENTO: Revista de Ciencias del Ejercicio y la Salud, 12 (1), 1-16. Los materiales curriculares juegan un papel importante en la construcción del concepto del cuerpo debido a que son transmisores de conocimientos, ideas y valores. El objetivo del estudio consiste en analiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…2, the data showed that children tend to choose activities in line with their gender roles, with a higher female participation in sports socially perceived as feminine, like dancing (94.1% girls vs. 5.9% boys; p < 0.001) or rhythmic gymnastics (93.1% girls vs. 6.9% boys; p < 0.001), while males participated more in sports socially perceived as masculine, like football (97.8% boys vs. 2.2% girls; p < 0.001) or wrestling sports (85.7% boys vs. 14.3% girls; p < 0.001) [42,43]. Furthermore, girls also participated more than boys in skating (80% girls vs. 20% boys; p = 0.005) and water sports (64.9% girls vs. 35.1% boys; p = 0.012), and boys enrolled more in handball (88.9% boys vs. 11.1% girls; p = 0.02) and racket sports (86.7% boys vs. 13.3% girls; p = 0.004), which is in line with the literature previously mentioned, where a greater tendency of boys to practice team sports was reflected in contrast to girls, who tended to practice individual ones [10,11,44]. These results are similar to those found in other studies that analyzed children's sports preferences [16,45,46] and seem to remain true throughout life [47].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…2, the data showed that children tend to choose activities in line with their gender roles, with a higher female participation in sports socially perceived as feminine, like dancing (94.1% girls vs. 5.9% boys; p < 0.001) or rhythmic gymnastics (93.1% girls vs. 6.9% boys; p < 0.001), while males participated more in sports socially perceived as masculine, like football (97.8% boys vs. 2.2% girls; p < 0.001) or wrestling sports (85.7% boys vs. 14.3% girls; p < 0.001) [42,43]. Furthermore, girls also participated more than boys in skating (80% girls vs. 20% boys; p = 0.005) and water sports (64.9% girls vs. 35.1% boys; p = 0.012), and boys enrolled more in handball (88.9% boys vs. 11.1% girls; p = 0.02) and racket sports (86.7% boys vs. 13.3% girls; p = 0.004), which is in line with the literature previously mentioned, where a greater tendency of boys to practice team sports was reflected in contrast to girls, who tended to practice individual ones [10,11,44]. These results are similar to those found in other studies that analyzed children's sports preferences [16,45,46] and seem to remain true throughout life [47].…”
Section: Discussionsupporting
confidence: 87%
“…The results from various past studies show that girls tend to prefer activities related to body shape and health with a more aesthetic orientation, preferring individual sports, while boys tend to opt for activities focused on improving fitness or physical performance, choosing team sports in which strength and competitiveness predominate [10,11].…”
Section: Introductionmentioning
confidence: 99%